2010
DOI: 10.1364/oe.18.003700
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear refractive index of porcine cornea studied by z-scan and self-focusing during femtosecond laser processing

Abstract: We have investigated the nonlinear refractive index of ex-vivo pig cornea by a combined approach using the standard z-scan technique on extracted corneas or corneal slices, as well as studying the deviations caused by self-focusing during femtosecond laser processing of the pig eyes. The experiments yield consistently an upper limit of 1.2 MW for the critical power of self-focusing in porcine cornea, and a value of 2 x 10(-19) m(2)/W for its nonlinear refractive index. We also demonstrate that due to this nonl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Although it has been shown that solid model systems such as gelatin or fused silica [34,35] are better suited than water [36], for example, they do not account for inhomogeneities of the corneal tissue and inter-subject variations [36,37]. Especially, nonlinear phenomena such as self-focusing depend critically on actual tissue properties and focusing conditions [36,38]. Furthermore, a recent study has shown that there is a difference in visual outcome between laser patterns which are centrifugally or centripetally applied [39].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that solid model systems such as gelatin or fused silica [34,35] are better suited than water [36], for example, they do not account for inhomogeneities of the corneal tissue and inter-subject variations [36,37]. Especially, nonlinear phenomena such as self-focusing depend critically on actual tissue properties and focusing conditions [36,38]. Furthermore, a recent study has shown that there is a difference in visual outcome between laser patterns which are centrifugally or centripetally applied [39].…”
Section: Discussionmentioning
confidence: 99%
“…These high intensities are capable of changing the optical properties of the tissue, including birefringence. 21 Therefore, it is important to measure the birefringence using a clinically relevant FSL. Additionally, our intention is not to map or image the corneal birefringence, but rather to sample the central cornea to generate a reference point for the laser parameters associated with this FSL.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the pig cornea has a nonlinear refractive index of 2·10 −19 m 2 /W, which is relatively high, compared to water [9]. This means that a precise calculation of the focal position can only be done by taking into account self-focusing effects.…”
Section: Methodsmentioning
confidence: 99%